Indigenous Business Support Services: A Case Study of the Quebec Entrepreneurial Ecosystem in Canada - Fortin-Lefebvre, Émilie; Baba, Sofiane (Journal of Aboriginal Economic Development, 2020)
Support services - also known as accompaniment practices and advisory services - are essential for the development of small businesses. In terms of support services specific to Indigenous businesses, the literature is rather silent. Yet, one can expect that the recent and growing market-related entrepreneurial trend in Indigenous communities will generate increasing accompaniment needs in those contexts. The objective of this research is to better understand the entrepreneurial ecosystem and its current synergy, as well as identifying the challenges of Indigenous entrepreneurship. To do so we rely on a qualitative methodological approach, focusing on the Indigenous entrepreneurial ecosystem in Quebec, Canada. Overall, our research highlights the need to adapt support services to Indigenous-related entrepreneurial issues. This research paves the way for a broader discussion related to how local governments, economic development organizations, funding agencies, and business support services organizations can work together for a comprehensive economic development strategy within Indigenous contexts.